Virome of Terrestrial Mammals and Bats from Southern Brazil: Circulation of New Putative Members of the Togaviridae Family and Other Findings - Julyana Sthéfanie Simões Matos; Meriane Demoliner; Juliana Schons Gularte; Micheli Filippi; Vyctoria Malayhka de Abreu Góes Pereira; Mariana Soares da Silva; Matheus Nunes Weber; Marcelo Pereira de Barros; Fernando Rosado Spilki (Pathogens)
The surveillance of wildlife viromes is essential for identifying zoonotic threats within the One Health framework. This study analyzed rectal and oral swabs from 88 individuals representing 13 species as felids, wild rodents, marsupials and non-human primates in Southern Brazil using metagenomic sequencing. Akodon montensis (n = 15 individuals) and Coendou spinosus (n = 4) harbored Chikungunya virus (ChikV, Togaviridae), marking its first detection in these hosts. Molossus molossus (n = 17) presented Coronaviridae and Orthoherpesviridae, while Eptesicus furinalis (n = 1) also carried Coronaviridae. A broad virome diversity, including Togaviridae and Adenoviridae members, was identified in Didelphis albiventris (n = 43), with significant relevance to human health. Additional species, such as Callithrix jacchus (n = 1), Leopardus guttulus (n = 1), Myocastor coypus (n = 1), Monodelphis iheringi (n = 1), Thaptomys nigrita (n = 1), Sooretamys angouya (n = 1), Brucepattersonius iheringi (n = 1), and Lasiurus blossevillii (n = 1), contributed to insights into viral reservoirs. These results underscore the importance of virome studies in regions harboring high biodiversity, emphasizing genomic surveillance as a vital tool for monitoring zoonotic viruses and safeguarding global health.